The Development of Community-Based Ecotourism in Border Area of Sambas Regency - Herlina Herlina; Eva Dolorosa; Dewi Kurniati (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Community-based ecotourism is a strategy done to develop an area through the improvement of the tourism sector by offering natural tourism sites that preserving the environment and involving the community skill in managing the tourism activities. This study aimed to identify the development of the community-based ecotourism in the border area of Sambas Regency. There were 30 key participants involved in this study. A questionnaire consisted of four main criteria (environmental, economy, social, and facility) employed in this study which then analyzed by the AHP technique. Statistical analysis showed that the economy criteria was having the highest weight with a total of 0.535, followed by the environmental, facility, and social criteria with a total of 0.287, 0.105, and 0.074 respectively. There were three alternatives of community-based ecotourism analyzed to improve the community income: beach, turtle, and mangrove ecotourism. The statistical analysis showed that beach ecotourism gained the highest score to be placed as an alternative priority (0.593).